The Assassin - Cussler, Clive; Scott, Justin; Brick, Scott; Jaffe, Sarah, 1986-; Thornburn, Cathy; Penguin Audio (Firm) ([New York] : Penguin Audio, 2015)
As Van Dorn private detective Isaac Bell strives to land a government contract to investigate John D. Rockefeller's Standard Oil monopoly, the case takes a deadly turn. A sniper begins murdering opponents of Standard Oil, kills Bell's best witness, a brave and likable man. Then the shooter detonates a terrible explosion that sets the victim's independent refinery ablaze. Bell summons his best detectives to scour the site of the crime for evidence.
Keywords: Bell, Isaac (Fictitious character) -- Fiction; Private investigators -- Fiction; Assassins -- Fiction; Audiobooks; Audiobooks; Mystery fiction; Suspense fiction